PENGARUH MODEL PEMBELAJARAN ARGUMEN-DRIVEN INQUIRY (ADI) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Rosyidah, Aminatur Rosyidah; Susilo, Herawati; Suwono, Hadi (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2023)
This research aims to know the influence of the ADI model against the critical thinking skills of students. Design research is quasi experimental with pretest-posttest control group design of non equivalent. The population are all grade X SMAN 06 Malang students consisting of 4 classes. Total sample are 2 experiment classes with ADI model treatment and 2 control classes with conventional learning assigment using simple random sampling. Critical thinking skills data are obtained from essay test carried out at the beginning and at the end of learning. Test results measured based on the indicators rubrics critical thinking skills further analyzed using Anacova with 0.05 significance level. The results showed that the ADI model affect students critical thinking skills.